Predictors of early introduction of complementary feeding: Longitudinal study - Tang, L.; Lee, A.; Binns, Colin (Blackwell Publishing, 2015)
Background Early introduction of complementary foods prior to 6 months of age may shorten breast-feeding duration and expose the infant to increased risk of morbidity and mortality. The aims of this study were to document the ages of complementary food introduction and to identify the determinants associated with early introduction of complementary feeding in Sichuan Province. Methods A prospective study on infant feeding practices was conducted during 2010-2011 in Jiangyou, China. A total of 695 mothers were recruited and interviewed at discharge. The follow-up interviews were carried out by telephone at 1, 3 and 6 months postpartum. Cox regression analysis was performed to determine factors related to early introduction of complementary feeding. Results The median age at start of complementary feeding was 4.5 months (95% confidence interval [CI]: 4.4-4.6 months). Mothers who perceived that most of their friends breast-fed (adjusted hazard ratio [HR], 0.70; 95%CI: 0.58-0.84) and those who returned to work when the infants were at least 6 months old were less likely to initiate complementary feeding early (adjusted HR, 0.73; 95%CI: 0.58-0.91), while infants who had been introduced to infant formula regularly before 6 months of age were at a higher risk of receiving complementary foods prematurely (adjusted HR, 1.81; 95%CI: 1.42-2.31). Conclusions Introducing complementary feeding before 6 months postpartum was widely practiced in Jiangyou. The appropriate age at which to introduce complementary foods and its benefits need to be emphasized in the future breast-feeding education strategies in Sichuan.